PENGARUH EFIKASI DIRI DAN EKSPEKTASI PENDAPATAN TERHADAP MOTIVASI BERWIRAUSAHA SISWA SMK KARTINI SINTANG - Husni Syahrudin (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
In entrepreneurship, motivation is non-negotiable. Motivation is very important because not everyone has the courage and ability to decide to become an entrepreneur. Entrepreneurial motivation is closely related to beliefs and expectations, or expectations of income from business activities. Higher income expectations encourage someone to become an entrepreneur. The purpose of this study was to describe the effect of self-efficacy expectations and income expectations on entrepreneurship of SMK Kartini Sintang students based on theoretical and empirical research. In this study, the research method used is correlative. The sample size for this study was 60 people. The survey method adopts indirect communication in the form of a questionnaire, and the weight of comments uses a Likert scale. Data analysis was carried out by quantitative calculations and analyzed using multiple regression analysis. Based on the research conducted, income expectations and income expectations partially affect the entrepreneurial spirit of SMK Kartini Sintang students. Meanwhile, the income expectations of SMK Kartini Sintang and the income expectations for students' entrepreneurship motivation